Socio-demographic Determinants of Attendance in Diabetes Education Centres: A Survey of Patients’ Views - M Lawal; A Woodman (European Medical Journal Diabetes, 2021)
Introduction: Diabetes is a global medical condition associated with a huge human and financial cost. However, early detection and appropriate pharmacological and non-pharmacological interventions, such as structured patient education, are useful measures to reduce its impact. Although the benefits of educational intervention are well recognised as a key component of empowerment, motivating attendance in diabetes education centres remains problematic, and this has a negative impact on healthcare finances. Objective: This survey study sought to identify the socio-demographic determinants of attendance at diabetes education centres. Methods: A questionnaire survey of 207 patients from four diabetes education centres was conducted. Results: In predicting attendance from demographic variables, the regression analysis showed that the participants that were living alone are less likely to attend, while participants who have a flexible working environment are more likely to attend the sessions.